Build A Web-Based E-Commerce Information System Using Content Management System (CMA) at Djuwariyah Accountant Service Office - Rafi Ardo; Mohamad Hasanudin; Afiat Sadida; Musyafa Al Farizi Farizi (Yayasan Ilomata, 2020)
The purpose of this research is to design and build a web-based e-commerce information system using a Content Management System (CMS) that can provide informative information, make transactions online, and expand market coverage. The system is built using CMS WordPress. The method used in system development is a prototype method with the system modeling language used is Unified Modelling Language (UML). The results obtained are a web company that provides informative information about the company profile and can conduct online service orders transactions.Keywords: Office of accountant Services, E-Commerce, CMS, prototype